A comprehensive study on electrochemical performance of Mn-surface-modified LiNi0.8Co0.15Al0.05O2 synthesized by an in situ oxidizing-coating method - Huang, Bin; Li, Xinhai; Wang, Zhixing; Guo, Huajun; Shen, Li; Wang, Jiexi (Journal of power sources, 2014)
The degradation of Ni-rich LiNi0.8Co0.15Al0.05O2 cathode material is successfully suppressed via a facile in situ oxidizing-coating method. KMnO4 is used as not only a Mn source but also an oxidant. X-ray diffraction (XRD) and scanning electron microscope (SEM) results demonstrate that the structure and morphology of the KMnO4-pretreated sample are the same as the pristine one. X-ray photoelectron spectroscopy (XPS) confirms that the valence state of Mn is +4 and the Ni3+ ions are partly reduced to Ni2+ when the material is doped with Mn4+. Besides, the Mn4+ ions are proved to distribute uniformly on the surface of the materials particles through energy dispersive spectrometer (EDS) and EDS elemental mapping. And it is confirmed that the concentration of Ni in the outer layer is reduced by the Mn-surface-modification. From the electrochemical characterizations, it is confirmed that the presence of tetravalent Mn at the surface can suppress the capacity fading during charge–discharge cycles, even under elevated temperature and overcharge conditions, and can prevent the material from deterioration during storage in air. •Mn is uniformly doped at the surface of LiNi0.8Co0.15Al0.05O2 particles.•The capacity fading under room temperature and high temperature is suppressed.•The capacity fading under overcharge condition is suppressed.•The degradation during storage in air is delayed.